Chinese GDP Forecast Using ARIMA Model - Ali, Fawaz Hamood Abdulazis Abdol (Universitas Negeri Medan, 2023)
China's economy is very interesting to analyze because it is recognized as the highest GDP inthe world. Despite the ability of China's economy to reform and grow, China shows fluctuationin its economy especially after the crisis in 1997 and 2008. When China was able to counterthe 2008 financial crisis, unfortunately starting from 2010 the GDP growth started to decreaseagain. Therefore, the objective of this research is to analyze the GDP of China in twoconsecutive years of 2016 and 2017 using the ARIMA. The journal that will be used uses atime series. time series is commonly used for series of data obtained chronologically. Thefuture value of a time series can most likely be predicted through its current and past values.This research uses EViews software. Eviews software can be called a combination of softwarespecifically made to process data on time series. This research also uses the ModelAutoregressive Integrated Moving Average (ARIMA) method, a time series estimationmethod, which can be used with EViews software. Based on the EViews software, theforecasting process with the ARIMA model is illustrated in this work, namely, China's GrossDomestic Product (GDP) estimated from 2016 to 2018.